Recent Progress in Relativistic Astrophysics 2019
DOI: 10.3390/proceedings2019017005
|View full text |Cite
|
Sign up to set email alerts
|

Parameterized and Consistency Tests of Gravity with GravitationalWaves: Current and Future

Abstract: Gravitational wave observations offer unique opportunities to probe gravity in the strong and dynamical regime, which was difficult to access previously. We here review two theory-agnostic ways to carry out tests of general relativity with gravitational waves, namely (i) parameterized waveform tests and (ii) consistency tests between the inspiral and merger-ringdown portions. For each method, we explain the formalism, followed by results from existing events, and finally we discuss future prospects with upgrad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 130 publications
(191 reference statements)
0
5
0
Order By: Relevance
“…See References [87][88][89] for studies projecting the possibilities of IMR consistency tests from combining information from current and future detectors. Especially, Reference [88] found that the multi-band observations can improve the constraints by a factor of 1.7. Analyze the signal by restricting the noise-weighted integral in the likelihood calculation to frequencies below and above the cut-off frequency, f cut .…”
Section: Inspiral-merger-ringdown Consistency Testmentioning
confidence: 99%
See 2 more Smart Citations
“…See References [87][88][89] for studies projecting the possibilities of IMR consistency tests from combining information from current and future detectors. Especially, Reference [88] found that the multi-band observations can improve the constraints by a factor of 1.7. Analyze the signal by restricting the noise-weighted integral in the likelihood calculation to frequencies below and above the cut-off frequency, f cut .…”
Section: Inspiral-merger-ringdown Consistency Testmentioning
confidence: 99%
“…This is illustrated in Figure 3 and see Reference [86] for more details of the method and demonstration on simulated binary signals. See References [87][88][89] for studies projecting the possibilities of IMR consistency tests from combining information from current and future detectors. Especially, Reference [88] found that the multi-band observations can improve the constraints by a factor of 1.7.…”
Section: Inspiral-merger-ringdown Consistency Testmentioning
confidence: 99%
See 1 more Smart Citation
“…A handful of tests have been already formulated and performed with merging BBH systems (see, for example, Refs. [88][89][90][91]), and we follow the (very) simple tests proposed by Nakano et al [66,92].…”
Section: The Implications For Tests Of Gr Via Multiband Observationmentioning
confidence: 99%
“…[27][28][29] examined the projected constraints on the bounds on dipolar GW radiation, Ref. [30] investigated the bounds on singleparameter tests of GR and Ref. [31] studied the constraints on the parameter space of modified theories of gravity using multiband observations.…”
mentioning
confidence: 99%